Eating disorder or disordered eating: undiagnosed inflammatory bowel disease mimicking eating disorder. Issue 10 (October 2019) - Harris, Rachel Elizabeth; Tayler, Rachel; Russell, Richard K
Abstract : We describe the case of a patient with ongoing weight loss, low mood and previously undisclosed gastrointestinal (GI) symptoms initially diagnosed with an eating disorder and subsequently diagnosed with ulcerative colitis over a year following initial presentation. This patient exhibited disordered eating secondary to the worsening symptoms of undiagnosed inflammatory bowel disease (IBD) and had altered her eating habits to reduce the diarrhoea and rectal bleeding she was experiencing, contributing to significant weight loss.The implications of a delayed diagnosis of IBD or incorrect diagnosis of eating disorder are severe both physically and psychologically. We discuss factors in the assessment of patients which may raise suspicion of organic GI disease such as IBD—an important differential diagnosis in those with non-specific GI symptoms and suspected eating disorder—and highlight baseline investigations which should be performed to ensure a diagnosis of IBD is not missed in these patients.